Pendampingan dan Penguatan Kemampuan Baca al-Qur’an pada Anak di Perumahan Pondok Permata Suci Gresik - Muhammad Arif Syihabuddin; Saskia Nabilah Awwaliyah (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service aims to improve the quality of reading the Qur'an by applying the knowledge of tajwid to children in pondok permata suci manyar Gresik. The purpose of this mentoring activity is to improve the quality of children in reading the Qur'an and understanding the science of recitation. The importance of this mentoring activity is that children can participate in mentoring activities actively and enthusiastically with interesting and varied methods. Through this mentoring activity, it is expected to be able to arouse the enthusiasm of children in learning and understanding the science of recitation and to be applied when reading the Qur'an. This assistance uses several methods, by carrying out FGD (Focus Group Discussion), and evaluating activities at each meeting. The impact of this assistance is: a) Increasing children's motivation and activeness in learning tajwid; b) The learning process of tajwid becomes more effective and efficient; c) Able to apply the knowledge of tajwid that has been learned when reading the Qur'an; d) Able to develop the knowledge of tajwid for the surrounding community.